The rise and development of the science of economics in Tuva: 1953 to present - Balakina, Galina F. (The New Research of Tuva, 2020)
Focusing on the rise and development of economics in Tuva, the article traces three stages in its history: 1953 to 1996, when the foundations of systemic economic studies were laid; 1997-2005, when the numbers of economics majors increased; the latest one started in 2006, when the topic range of studies in economics began to expand, and the main directions, organizational structures and prospects of economics in the region were redefined. At the earliest stage, economic research was held at the Sector of Economics, Tuvan Research Institute of Language, Literature and History. Economists were consulted when the decision to raise the status of Tuvan Autonomous Oblast’ to Tuvan ASSR was being pondered, and the forms of interaction between administrative bodies and researchers in economics were ultimately developed. In 1960s and 1970s the first dissertations of Tuvan economy were defended. The second stage, which started in late 1990s, saw the much-improved training of economists and other type of researchers. They now form the core of professionals managing enterprises, industry branches, financial institutions, ministries and government agencies. At the contemporary stage of the science of economics in Tuva, the number of professional economists with a university degree is quite high, as well as that of academic researchers. Many of them are on the staff list of Tuvinian Institute for Exploration of the Natural Resources SB RAS.